1996
DOI: 10.3758/bf03205481
|View full text |Cite
|
Sign up to set email alerts
|

Illusory form with inducers of opposite contrast polarity: Evidence for multistage integration

Abstract: The perception of brightness differences in Ehrenstein figures and of illusory contours in phaseshifted line gratings was investigated as a function of the contrast polarity of the inducing elements. Wepresented either continuous lines or line-like arrangements composed of aligned dashes or dots whose spacing was varied. A yes/no procedure was used in which naive observers had to decide whether or not they perceived a brightness difference in a given Ehrenstein figure or an illusory contour in a phase-shifted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
3
27
1
Order By: Relevance
“…For example, Murray et al (2002) identified the onset of the IC effect at ~90ms and localized it to the LOC. This 'brain signature' of IC sensitivity is robust across a range of stimulus/perceptual variations: contrast polarity ; see also Dresp et al, 1996 for psychophysical findings), modal vs. amodal completion (i.e. whether or not there was a perceived brightness enhancement; Murray et al, 2004), accuracy in discriminating convex versus concave shapes created by the ICs (Murray et al, 2006), or the stimulus type eliciting the ICs (Kanizsa-type stimuli or misaligned gratings; Knebel and Murray, 2012;Mendola et al, 1999).…”
Section: Brain Mechanisms Of Ic Sensitivity Across Types Of Contrastmentioning
confidence: 99%
“…For example, Murray et al (2002) identified the onset of the IC effect at ~90ms and localized it to the LOC. This 'brain signature' of IC sensitivity is robust across a range of stimulus/perceptual variations: contrast polarity ; see also Dresp et al, 1996 for psychophysical findings), modal vs. amodal completion (i.e. whether or not there was a perceived brightness enhancement; Murray et al, 2004), accuracy in discriminating convex versus concave shapes created by the ICs (Murray et al, 2006), or the stimulus type eliciting the ICs (Kanizsa-type stimuli or misaligned gratings; Knebel and Murray, 2012;Mendola et al, 1999).…”
Section: Brain Mechanisms Of Ic Sensitivity Across Types Of Contrastmentioning
confidence: 99%
“…In earlier experiments (Dresp et aI., 1996), such figures were used to study illusory brightness perception as a function of local variations in stimulus geometry, with an emphasis on assumptions concerning the underlying feature integration mechanisms. These figures were found to produce a variety ofillusory percepts covering a wide range ofdifferent, discriminable, illusory strengths (see Dresp et a\., 1996).…”
Section: Stimulimentioning
confidence: 99%
“…Subjective magnitude was determined in a first experiment by a cross-modality matching procedure like the one used by Dresp, Lorenceau, and Bonnet (1990) in a study of the perception of apparent brightness in the Kanizsa square. In a second experiment, we measured the time necessary to perceive the presence or the absence of an apparent surface in these same illusory figures, replicating the procedure used by Dresp et al (1996). We found that subjective magnitude, response time, and frequency of perception provide complementary data reflecting different aspects of information processing involved in the perception of brightness illusions.…”
mentioning
confidence: 99%
See 2 more Smart Citations